The starfish and the spider the unstoppable power of leaderless organizations - Brafman, Ori. (New York Portfolio, 2006)
Includes information on Alcoholics Anonymous, al Qaeda, Amazon, Animal Liberation Front, Apaches, eBay, General Motors, Goodwill Industries, Google, Grokster, Kazaa, music piracy, Napster, P2P (peer to peer) services, Quakers, record industry, U.S. Supreme Court, Wikipedia, etc.
Includes bibliographical references (p. 211-217) and index.
Keywords: Decentralization in management